2020
DOI: 10.1136/bmjopen-2019-035926
|View full text |Cite
|
Sign up to set email alerts
|

aDolescent and prEconception health peRspectiVe of Adult Non-communicable diseases (DERVAN): protocol for rural prospective adolescent girls cohort study in Ratnagiri district of Konkan region of India (DERVAN-1)

Abstract: IntroductionPrecise impact of nutritional insufficiencies in adolescence as a risk factor for non-communicable diseases (NCD) in later life as adults remains largely unknown.We are conducting research into the effects of nutrition on adolescent girls of Ratnagiri district by a prospective cohort study (aDolescent and prEconception health peRspectiVe of Adult Non-communicable diseases cohort). Our study focuses on the physical health, nutritional parameters and cognitive profiles of adolescent girls, during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several cross-sectional studies have found that iron intake is significantly associated with anemia. Based on the current findings, this warrants an emphasis on creating a conducive school environment that encourages healthy eating with sufficient nutrition to halt bodily health and prevent malnutrition (Patil et al, 2020;Saeedi et al, 2018).…”
Section: Relationship Between Dietaty Habit and Anemia Incidence In A...mentioning
confidence: 81%
“…Several cross-sectional studies have found that iron intake is significantly associated with anemia. Based on the current findings, this warrants an emphasis on creating a conducive school environment that encourages healthy eating with sufficient nutrition to halt bodily health and prevent malnutrition (Patil et al, 2020;Saeedi et al, 2018).…”
Section: Relationship Between Dietaty Habit and Anemia Incidence In A...mentioning
confidence: 81%
“…( 26 ) To the best of the researcher's knowledge, no cohort study has investigated the longitudinal relationship of nutritional status and anaemia among adolescents from early until late adolescence to date worldwide. Often, these cohort studies were analysed cross-sectionally either looking at single nutrients like the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) study,( 27 ) adolescent preconception health in the aDolescent and prEconception health peRspectiVe of Adult Non-communicable diseases (DERVAN) study ( 28 ) or dietary pattern. ( 29 )…”
Section: Discussionmentioning
confidence: 99%
“…The details of DERVAN cohort study have been already reported [7]. It plans to recruit more than 1500 adolescent girls (age16-18 years) from three tehasils (administrative divisions) of Ratnagiri district.…”
Section: Methodsmentioning
confidence: 99%
“…This manuscript explores the bone health of adolescent girls from cohort study (DERVAN cohort) using biochemical indicators. The study is taking place in the Konkan region of western Indian state of Maharashtra [7].…”
Section: Introductionmentioning
confidence: 99%